Antibacterial and Antifungal Activities of Patikan Kebo (Euphorbia Hirta L.) Herb Ethanol Extract - Simanjuntak, Helen Anjelina; Rahmiati, Rahmiati (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: The aim of this study was to determine the content of secondary metabolites, and the concentration of extracts that were effective as antibacterial and antifungal agents. Methods: The research method was carried out experimentally with several stages; making Simplicia, Simplicia characterization, maceration, phytochemical screening, making test solutions, and testing antibacterial and antifungal activities. Results: The results of phytochemical screening of the ethanol extract of the patikan kebo herb (Euphorbia hirta L.) showed the existance of alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. Furthermore, the results of the antibacterial and antifungal activity test showed that the ethanol extract of the patikan kebo herb showed the diameter of the inhibition zone in the Strong category as the concentration increased. Conclusion: The herbal extract of patikan kebo (Euphorbia hirta L.) has antibacterial and antifungal activity so that it has potential as a natural antibiotic.